Outcomes of simultaneous pancreas and kidney transplantation based on donor resuscitation. Issue 6 (27th February 2020) - Messner, Franka; Etra, Joanna W.; Yu, Yifan; Massie, Allan B.; Jackson, Kyle R.; Brandacher, Gerald; Schneeberger, Stefan; Margreiter, Christian; Segev, Dorry L.
Abstract : It has been hypothesized that transplanting simultaneous pancreas kidney (SPK) grafts from donors with a history of cardiac arrest and cardiopulmonary resuscitation (CACPR) leads to inferior posttransplant outcomes due to organ hypoperfusion during cardiac arrest and mechanical trauma during resuscitation. Using Scientific Registry of Transplant Recipients data, we identified 13 095 SPK transplants from 2000‐2018, of which 810 (6.2%) were from donors with a history of CACPR. After inverse probability of treatment weighting on donor and recipient characteristics, we found that 1‐, 5‐, and 10‐year patient (CACPR: 96.4%, 89.9%, and 78.9%; non‐CACPR: 96.3%, 88.9%, and 76.0%; P  = .3), death‐censored pancreas graft survival (CACPR: 89.3%, 82.7%, 75.0%; non‐CACPR: 89.9%, 82.7%, 76.3%; P  = .7), and death‐censored kidney graft survival (CACPR: 97.0%, 89.5%, 78.2%; non‐CACPR: 96.9.9%, 88.7%, 80.0%; P  = .4) were comparable between the two groups. There were no differences in the risk of pancreatitis (CACPR: 2.9%, non‐CACPR: 2.4%; weighted OR = 0.74 1.22 2.02 ; P  = .4), anastomotic leak (CACPR: 1.6%, non‐CACPR: 2.0%; weighted OR = 0.54 1.02 1.93 ; P  > .9), or median length of hospital stay (CACPR: 8 days, non‐CACPR: 9 days; P  = .6) for recipients of CACPR vs non‐CACPR donors. Our findings suggest that CACPR donors could be used to expand the SPK donor pool without compromising short‐ or long‐term outcomes. Abstract : This national study of 13, 095 simultaneous pancreas‐kidney transplants found similar patient survival, pancreas and kidney graft survival, and occurrence of postoperative complications in recipients of organs from donors with and without a history of cardiac arrest and resuscitation, suggesting that these donors could be used to expand the donor pool without compromising short‐ or long‐term outcomes.